DETERMINATION OF WORK CULTURE, WORKLOAD, AND WORK ETHOS WITH JOB SATISFACTION AS AN INTERVENING VARIABLE ON WORK EFFECTIVENESS AT THE REGIONAL SECRETARIAT OF PROVINCE KEPULAUAN RIAU - Franto Tonggi Tampubolon; Chablullah Wibisono; Mohamad Gita Indrawan; Muammar Khaddafi (CV. Radja Publika, 2023)
The purpose of this study was to determine and analyze the effect of work culture, workload, and work ethic on work effectiveness and job satisfaction as an intervening variable. The method used in this study is a causal model survey method, data collection using a questionnaire and distributed to 217 respondents. Statistical data analysis using SEM-PLS (Structural Equation Modeling - Partial Least Square) and using path analysis to test the pattern of relationships that reveal the influence of variables on other variables, both direct and indirect effects with the help of Smart PLS Ver.3.0 software. Results in the study this shows that work culture has a direct positive and insignificant effect on job satisfaction with a P-value of 0.425 > 0.05.